Interface protocol design: a communication guide for indoor FANET - B.O. Sadiq; A. T. Salawudeen; Y. A. Sha’aban; E. A. Adedokun; M. B. Mu’azu (Universitas Ahmad Dahlan, 2019)
The present and the future routing protocols in relation to the high throughput requirement, adaptivity to fast-changing link topology and speed makes the choice of routing protocol for unmanned aerial vehicle communication important. Due to this fact, an efficient routing protocol is highly dependent on the nature of the communication link. A flexible solution that presents these features is the use of light fidelity as a communication medium. Therefore, this paper presents the design of an interface protocol for indoor Flying Ad-hoc Network specific routing protocol using light fidelity as a communication link. The interface protocol governs communication when UAV move in a swarm. The architecture, the state machine model is discussed in this paper. Results of the design are validated via simulation using the NS3 in terms of packet delivery ratio and throughput.